(untitled) (ACME, 2024)
This paper deals with the reading προμηθέως to be find at the end of line 86 from Aeschylus’ (?) Prometheus. The aim is to appreciate the genuineness of the paradosis, compared to Peter Elsmley’s emendation προμηθίας.